The interplay between internal and external load parameters during different strength training sessions in resistance-trained men - Martorelli, André S; De Lima, Filipe D; Vieira, Amilton; Tufano, James J; Ernesto, Carlos; Boullosa, Daniel; Bottaro, Martim (European journal of sport science, 2021)
External load influences internal load in resistance training (RT). The purpose of the present study was to compare the total volume-load, perceptual and stress responses during three different RT protocols. Twelve resistance-trained men completed three different RT protocols with the back squat and bench press exercises: (1) power (POW) (5 sets of 6 repetitions at 50%1RM, 2-min of rest), (2) hypertrophy (HYP) (5 sets-to-failure at 75%1RM, 2-min of rest), and (3) strength (STR) (5 sets-to-failure at 90%1RM, 3-min of rest). Volume-load (kg × reps.), session rating of perceived exertion (sRPE), training impulse (TRIMP; reps. × sRPE), cortisol, immunoglobulin A (IgA), lactate, and creatine kinase (CK) were assessed before and/or after the sessions. HYP was the most demanding session in terms of volume-load (p < 0.001), TRIMP (p < 0.001), cortisol (p = 0.001), lactate (p < 0.001), and CK (p = 0.001). Despite POW exhibited a greater volume-load than STR (p = 0.016), the latter exhibiting a greater sRPE (p < 0.001), and a greater post-session CK (p = 0.05). However, the TRIMP of STR and POW were not statistically different (152 vs. 260 AU; p = 0.089). These specific responses could be meditated by the presence of muscular failure. When pooling all the sessions, significant correlations were revealed among external and internal stress markers (r = 0.35-0.80; p ≤ 0.05). The use of TRIMP could be recommended as a simple and valid monitoring tool which integrates into a single parameter the internal and the external loads of RT sessions.
Keywords: Creatine Kinase; Young Adult; Analysis of Variance; Lactic Acid; Male; biologické markery; odporový trénink; Muscle Development; Biomarkers; mladý dospělý; Adult; dospělí; mužské pohlaví; hypertrofie; hydrokortison; Resistance Training; svalová síla; vývoj svalů; Hydrocortisone; Muscle Strength; kyselina mléčná; lidé; analýza rozptylu; Humans; tělesná námaha; imunoglobulin A; kreatinkinasa; Hypertrophy; vzpírání; Immunoglobulin A; Weight Lifting; Physical Exertion